Exploring the therapeutic potential: Malaysian channa striatus water extract enriched with arachidonic acid for wound healing in human foetal lung cells (IMR-90) - Saiful Irwan Zubairi; Ngui, Winnie Shy Yi; Zalifah Mohd Kasim; Noraziani Zainal Abidin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Channa striatus, also known as haruan, is traditionally used in Malaysia for its wound-healing properties. This study evaluated the wound healing potential of Channa striatus water extract (CSWE) and identified key compounds promoting fibroblast cell growth. Channa striatus were deboned to maximize fillet retention. CSWE was obtained through aqueous extraction, and its physicochemical properties were analyzed, including pH, rheological characteristics, moisture content, amino acid composition, and arachidonic acid presence. The effective concentration (EC50) of the sample was determined using a 2-D cell culture system with human fibroblast cells (IMR-90) over three days. Results showed CSWE had a near-neutral pH (6.34 ± 0.01) and high moisture content (97.3 ± 0.01%). The extract displayed Newtonian fluid behavior with a viscosity of 1.50 ± 0.31 mPa.s. CSWE contained essential amino acid glycine and arachidonic acid, important for wound healing, but in low concentrations. These low concentrations did not significantly promote IMR-90 cell growth (p>0.05) compared to the control. Consequently, EC50 values for CSWE were invalid due to over-dilution from a high fish weight-to-solvent ratio. Despite this, IMR-90 cell growth rates remained consistent across different CSWE concentrations, with no observed mortality during the three-day incubation. Overall, IMR-90 cells exhibited insignificant growth, even with arachidonic acid and glycine at low concentrations during treatment.